High Drug Prices Hurt Everyone - Halpenny, Genevieve M. (ACS Med Chem Lett, 2016)
Turing Pharmaceuticals raised the price of Daraprim 5,500%, illustrating how the absence of competition in the sale of low-volume, low-price drugs can lead to price gouging. For patented medicines, society allows supracompetitive pricing to incentivize innovation. However, Gilead’s decision to sell Sovaldi for $84,000 per course of treatment raised the question whether society must accept any price set by the patent holder. Unfortunately, these incidents illustrate a broader trend in which pharmaceutical prices are greater in the United States than abroad, placing the United States at the top in per capita expenditures on pharmaceuticals. The Canadian and Indian approaches to balancing patient access to medicines with other policy objectives, including stimulating investment in R&D, point to a multifaceted solution. Proposed solutions include prevention, increasing pharmaceutical coverage, and increasing transparency. Strategic policy requires access to information regarding R&D costs, private listing agreements (prices charged to different customers), and patient outcomes.